Comparison of the incidence, nature and cause of injuries sustained on dirt field and artificial turf field by amateur football players - Kordi, R.; Hemmati, F.; Heidarian, E.; Ziaee, V. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2011)
Background Data on the incidence, nature, severity and cause of match football injuries sustained on dirt field are scarce. The objectives of this study was to compare the incidence, nature, severity and cause of match injuries sustained on dirt field and artificial turf field by amateur male football players.